Hybrid Torts and Explanatory Tort Theory - Murphy, John (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2018)
This article examines the problem of fit caused by “hybrid torts” for several contemporary, explanatory theories of tort law: those belonging to Ernest Weinrib, Robert Stevens, and John Goldberg and Benjamin Zipursky. The term hybrid tort is intended to capture a cause of action that is treated routinely by practitioners, judges and doctrinal jurists alike as a tort proper even though its ingredients suggest that it is only part tort and part something else (like, for example, equity). The central argument of the article is as follows: at tort law’s borders with other legal categories, there exists a number of hybrid actions that are widely acknowledged to be torts but which comprise a range of juridical components, some of which are typical within tort law and some of which are more germane to some other legal category. This set of hybrid actions suggests that—whatever theoretical neatness might dictate—tort law’s boundaries are fuzzy and porous, not clearly defined and rigid. This fuzziness in the object of theorization naturally casts doubt on the apple-pie neatness of the theories in view. In addition, the obvious response—that these juridically mixed causes of action are not proper torts (and therefore do not require explanation)—is shown to be unavailable to the theorists whose work is examined given that each of them commits to explaining the law as it presents itself. Put differently: since the law as we encounter it clearly treats these hybrid actions as torts, they cannot be dismissed in this way. Nor, it is argued—for a combination of reasons that establish their practical significance—can these hybrid torts be dismissed as irrelevant.